(untitled) (Revista Sistemas de Producción Agroecológicos, 2014)
The stingrays (family potamotrygonidae) are fish that inhabit the rivers of Colombia. No study has been conducted based on the problem of accidents and poisoning causing these animals. This work aims to contribute to the knowledge of the composition of the venom enzyme stripe Potamotrygom schroederi, proposing search 6 enzymes: protease, 5’-nucleotidase, acid and alkaline phosphatases, phospholipase A2 and hyaluronidase. The venom was isolated stripe Potamotrygom schroederi, obtained from Negro river (Meta). The stripes were captured and under anesthetic management harpoon was removed and then left alone, the barbs were stored in liquid nitrogen and then were lyophilized, which were scraped and weighed and homogenized content, then centrifuged at 10,000 rpm for 10 minutes at 4°C, obtaining by lysis of the cells, the poison. It worked as a positive control for testing the purified hyaluronidase, Bothrops asper venom in the region of Armero, obtained by milking the snakes kept in captivity at the Serpentarium of the National Institute of Health. The negative control for all tests was a target. The different enzymatic techniques were standardized and results determine the presence of 4 of the 6 enzymes originally proposed: proteases, 5-nucleotidase, alkaline phosphatase and hyaluronidase. Additionally, a profile accident took place in the Departmental Hospital Villavicencio, finding 20 cases, with the presence of symptoms such as tissue necrosis, edema and pain, triggering in amputation of the affected limb. The results indicate that the stripes are poisonous animals that have a direct bearing on human health, because their venom has an enzyme mixture that causes serious disturbances in various systems, with no effective treatment, why should be considered a public health problem by incorporating within the group of venomous animals of Colombia.